Penetapan Jasa Transfer Tunai Nasabah Melalui Agen BRILink Perspektif Hukum Ekonomi syariah (Studi di BRILink Desa Payolebar Kec. Singkut Kab. Sarolangun) - Alex Candra; Fauzi Muhammad; Jalaluddin Fatimah (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the determination of cash transfer service fees by BRILink agents in Payolebar Village, Singkut District, Sarolangun Regency, from the perspective of Islamic Economic Law.This research is an empirical legal study using a case study approach. The researcher used primary data obtained through observation, interviews, and documentation conducted at BRILink agents in Payolebar Village, as well as secondary data obtained from literature studies including journals, books, research reports, and other sources. Tertiary data were gathered from the Kamus Besar Bahasa Indonesia (KBBI), legal dictionaries, and various other dictionaries. The data processing and analysis technique used in this study is a qualitative descriptive approach, consisting of the following stages: data collection, data analysis, data reduction, data presentation, conclusion drawing, and research reporting. The findings of this study indicate that: First, the service fees set by each agent vary and are calculated based on electricity costs, rental costs, operational expenses, distance to the nearest ATM, and proximity to other agents. Second, from the perspective of Islamic Economic Law, the fee determination by BRILink agents in Payolebar Village can be deemed valid and in accordance with the ijarah contract (wage-based service agreement), fulfilling the principles of justice, transparency, mutual consent, cooperation, and benefit.